A vulnerabilidade do sujeito de pesquisa e o Termo de Consentimento Livre e Esclarecido - Santos, Mary Lee dos (2009)
Resolution 196/96 of Brazilian Health Ministry establishes conditions for research in human subjects and ensures their protection. This paper investigates subjects who participated in academic researches carried out in 2008, by health course undergraduate students, establishing the relationship between the subjects' knowledge about the research and their social background. Vulnerability is a much broader concept than the historical protection of the fragile, and as to adequately understand it today it is necessary to learn about subjects' social setting, access to health services and knowledge about the research. To safeguard confidentiality and privacy of researchers whilst carrying out a research within researches, the institutional Ethics Committee posed as mediator and invited researchers to participate in the study, only revealing their identities and contact information after they accepted to be in the study and granted access to subject in their studies. This resulted in approx 60% decline from participants who either did not accept, or did not answer or informed setbacks in researches previously approved by the Committee. From the remaining projects which met the criteria of the present study 50 subjects were proportionally selected to represent the population more frequently investigated: patients enrolled in group activities, health workers, health course students and elderly both from groups of patients or from nursing homes. 79% of subjects were from lower income classes (D and E) and despite higher education of 49% of subjects 60% of them never read the Informed Consent. It is necessary to renew the importance of Informed Consent as to educate volunteers about the the benefits and the risks from their participation, including information about their health conditions, thus allowing for better communication between subjects and researchers and further consideration of social vulnerability